1987
DOI: 10.1159/000167515
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lactate as a Base in Hemodialysis

Abstract: The purpose of our study was to investigate the feasibility of using lactate as a complete or partial substitute for acetate in hemodialysis solutions. Six patients, each serving as his own control, were dialyzed once against a dialysis solution containing 40 mM acetate, once against a dialysis solution containing 40 mM DL-lactate and once against a dialysis solution containing 20 mM each of acetate and DL-lactate. Six additional patients underwent hemodialysis using acetate+lactate for a 3-week period, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…They have been hailed as the LEGOs of the biochemical industry because so many different products can be produced from them . For instance, lactic acid is an excipient to control the pH in kidney dialysis in addition to being a monomer for generating poly­(lactide) (PLA) plastics, which are biodegradable and easy to recycle due to their labile ester bonds. Ferulic acid is used as an antioxidant fuel stabilizer in the biofuel industry, , and itaconic acid is used in the manufacturing of plexiglass.…”
Section: Introductionmentioning
confidence: 99%
“…They have been hailed as the LEGOs of the biochemical industry because so many different products can be produced from them . For instance, lactic acid is an excipient to control the pH in kidney dialysis in addition to being a monomer for generating poly­(lactide) (PLA) plastics, which are biodegradable and easy to recycle due to their labile ester bonds. Ferulic acid is used as an antioxidant fuel stabilizer in the biofuel industry, , and itaconic acid is used in the manufacturing of plexiglass.…”
Section: Introductionmentioning
confidence: 99%
“…We began feasibility studies in patients using DLlactate as a dialysis solution base. We found that a dialysis solution containing 40 mM DL-lactate resulted in insufficient correction of acidosis ( 13,14). A reduction in symptoms with lactate was not found erans Administration Hospital, Hines, IL 60141,…”
mentioning
confidence: 95%